Curbing the car: the mitigation potential of a higher carbon price in the New Zealand transport sector. (27th May 2020) - Hasan, Md Arif; Frame, David J.; Chapman, Ralph; Archie, Kelli M.
ABSTRACT: Carbon dioxide emissions from New Zealand's transport sector have experienced rapid growth since 1990. In this paper, we investigate the scope for a targeted price signal to curb emissions growth and help deliver on the country's Paris Agreement pledges. Cost burdens on various income groups are investigated, and experts' opinions are elicited to evaluate two types of carbon price policies (i.e. a carbon tax and an increase in the current ETS price). We use two methodological approaches in this paper. Estimates of the social cost of carbon and the price elasticity of fuel demand are used to understand the mitigation potential of a higher carbon price, while a multi-criteria analysis technique is used to understand experts' preferences between an ETS and a carbon tax. The findings are that with a price elasticity of transport fuel demand of around −0.7, a carbon price between NZD 100 (USD 65) per tonne of carbon dioxide (tCO2 ) and NZD 235 (USD 153)/tCO2 could reduce transport emissions by between 33% and 44% in 2030, respectively, from the 2016 level. The (uncompensated) cost-burdens on lower income households due to a hypothetical price of NZD 100/tCO2 and NZD 235/tCO2 are estimated to be around NZD 531 (USD 345)/year and NZD 670 (USD 436)/year per household respectively. Experts marginally favoured a carbon tax over an ETS because the revenue collected through a carbon tax could be utilized in a more holistic way to offset the tax burden on lower income households and fund emissions reduction technologies and infrastructures. Key policy insights A carbon price of NZD 235 (USD 153)/tCO2 implying a fuel price of NZD 3/litre (USD 1.95/litre) could reduce transport emissions by 44% in 2030 from the 2016 level. A fuel price of NZD 3/litre is comparable to fuel prices in the early 1980s, when these were at a historic high. A carbon price of NZD 235 (USD 153) would increase the annual domestic transport expenditure of lower income households by NZD 670 (USD 436), a 42% increase. A carbon tax is marginally preferred by interviewed experts to an increase in prices under the current ETS.